Temperature changes on Balkan peninsula between 1961 and 2018 - Tjukajev, Patricija (Journal for Geography, 2021)
Temperature changes on Balkan peninsula between 1961 and 2018In this paper, we present the changes in air temperatures in the Balkan Peninsula in the period 1961–2018. We included in the study area countries that fully or mostly meet the criteria of natural-geographical and socio-geographical definition of the Balkan Peninsula. Changes in average minimum and maximum seasonal air temperatures were analysed and mapped. With the help of spatial analysis of the trend, we also mapped the areas of intensive increase in air temperatures. The findings showed an increase in average minimum and maximum air temperatures in all seasons throughout the Balkan Peninsula.